The influence of the trade-off between profitability and future increases in sales on cost stickiness - Josep Maria Argilés-Bosch; Josep García-Blandón; Diego Ravenda; Maika M. Valencia-Silva; Antonio D. Somoza (Estudios de Economía, 2017)
This study analyses cost stickiness under the dilemma between current profitability and future sales increase. When activity decreases firms are faced to keep profitability adjusting resources, while they should also consider long term consequences and keep slack resources which allow building firms capacities to adapt to external challenges and take advantage of future opportunities. We find empirical evidence that changes in current firm profitability and one year ahead sales increase significantly influence resource adjustment in periods when sales decrease. We find a significant moderating effect of changes in profitability, as well as a significant stressing effect of one year ahead sales increase, on cost stickiness.
Keywords: M41; M21; M10; 330; Cost stickiness; profitability; increases in sales; slack; resource adjustment